Photophysical property trends for a homologous series of bis-ethynyl-substituted benzochalcogendiazoles - Coombs, Benjamin A.; Lindner, Benjamin; Rominger, Frank; Bunz, Uwe H. F. (New journal of chemistry, 2012)
We report on the preparation and photophysical property study of three homologous benzoheteroarene-ethynylene systems. Significant differences in the series' optical properties indicate a change in the HOMO-LUMO energy as the chalcogen is altered (O, S and Se) which we have examined using TD-DFT methods and shown to be attributable to modification of the HOMO energy.